2021
DOI: 10.3390/su13031504
|View full text |Cite
|
Sign up to set email alerts
|

Irrigation Management in Potato (Solanum tuberosum L.) Production: A Review

Abstract: Limited water resources coupled with the increase of the human population calls for more efficient use of water in irrigated agriculture. Potato (Solanum tuberosum L.) is one of the most widely grown crops worldwide and is very sensitive to water stress due to its shallow rooting system. With the dilemma of potato sensitivity to drought and limited available water resources restricting crop production, researchers and crop growers have been investigating different approaches for optimizing potato yield and imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
53
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(58 citation statements)
references
References 153 publications
3
53
1
1
Order By: Relevance
“…Begum et al (2018) found that supplemental irrigation is very important for potato in the areas with a high drought frequency due to the high yield of potato in a short time and if shortage of readily available water in the soil is eliminated it is possible to achieve high and stable potato yield of 40-50 t/ha or more. Previous studies found an increase in tuber number/plant and marketable potato yield of irrigated potato compared to rain-fed production (Abu El-Fotoh et al 2019;Djaman et al 2021;Waqas et al 2021). Djaman et al (2021) also reported the highest tuber number/plant under full irrigation.…”
Section: Yield Componentsmentioning
confidence: 81%
See 1 more Smart Citation
“…Begum et al (2018) found that supplemental irrigation is very important for potato in the areas with a high drought frequency due to the high yield of potato in a short time and if shortage of readily available water in the soil is eliminated it is possible to achieve high and stable potato yield of 40-50 t/ha or more. Previous studies found an increase in tuber number/plant and marketable potato yield of irrigated potato compared to rain-fed production (Abu El-Fotoh et al 2019;Djaman et al 2021;Waqas et al 2021). Djaman et al (2021) also reported the highest tuber number/plant under full irrigation.…”
Section: Yield Componentsmentioning
confidence: 81%
“…Previous studies found an increase in tuber number/plant and marketable potato yield of irrigated potato compared to rain-fed production (Abu El-Fotoh et al 2019;Djaman et al 2021;Waqas et al 2021). Djaman et al (2021) also reported the highest tuber number/plant under full irrigation.…”
Section: Yield Componentsmentioning
confidence: 81%
“…Potato is consumed by humans under many different preparations-boiled, baked, fried, snack, chips, starch-and is a significant source of carbohydrates [3,4], protein [3,5,6], minerals [6], vitamin C [4], and phenolic compounds [6]. Potato crop is very sensitive to water stress [7][8][9], nitrogen fertilizer deficiency, and is subject to a wide variety of disorders and diseases. Aboveground disorders and diseases include early blight (Alternaria solani), late blight (Phytophthora infestans), Fusarium dry rot (Fusarium spp.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported that the optimum water requirements for achieving a high TTY in potato crops varies from 350 to 800 mm [15,18,87]. However, Ferreira and Carr [88] reported that the potato variety Desirée required 150-550 mm of irrigation water when growing under hot and dry climate conditions, while El-Abedin et al [16] showed that the water requirement of potato reached 1505 mm in Saudi Arabia, which is a typical example of an arid country.…”
Section: Impact Of the Irrigation Regime On The Growth Water Status And Production Of Potatomentioning
confidence: 99%
“…Potato is also a short-duration crop that produces large and sensitive foliage in response to soil moisture stress [10,11]. Several studies have confirmed that small errors in irrigation water management in potato production and exposure of potato plants to deficit irrigation, particularly during the sensitive growth stages, causes a tremendous reduction in the quantity and quality of tuber yield and the net economic return of the production system [12][13][14][15][16][17][18]. Consequently, correct irrigation water management is required to simultaneously maximize the yield and irrigation water use efficiency of potato under deficit irrigation conditions [18].…”
Section: Introductionmentioning
confidence: 99%